Presentation Essentials : The Tools You Need to Captivate Your Audience, Deliver Your Story, and Make Your Message Memorable - Bruce, Anne; Love, Sardek (McGraw-Hill's AccessEngineeringLibrary., 2023)
One of the first books in McGraw Hill's NEW Business Essentials Series providing a how-to guide to develop powerful, engaging, and effective presentations for today's new world of work.